1995
DOI: 10.1111/j.1399-6576.1995.tb04146.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid balance and pulmonary functions during and after coronary artery bypass surgery: Ringer's acetate compared with dextran, polygeline, or albumin

Abstract: The effects on fluid balance, pulmonary functions and economics were evaluated in a randomized comparison of one colloid free and three colloid containing fluid regimens, for 48 hours during and after coronary artery bypass (CAB) surgery. A standard regimen for anaesthesia, extracorporeal circulation and monitoring was used. Only Ringer's acetate (RAc) was used as priming solution for extracorporeal circulation. Forty patients were randomized to receive either RAc, polygeline 35 mg.ml-1 (Haemaccel), dextran 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 12 publications
2
23
2
Order By: Relevance
“…The findings of a similar fluid balance diverge from those in an investigation (Tølløfsrud et al 1995) claiming that a larger volume of crystalloids than of colloids is necessary to maintain hemodynamics (CI, PCWP, CVP). The Tølløfsrud group used colloids intraoperatively, and fluid retention was greater in the crystalloid group only at the end of surgery, but not at 48 hours postoperatively.…”
Section: Blood Loss and Fluid Balancecontrasting
confidence: 50%
See 1 more Smart Citation
“…The findings of a similar fluid balance diverge from those in an investigation (Tølløfsrud et al 1995) claiming that a larger volume of crystalloids than of colloids is necessary to maintain hemodynamics (CI, PCWP, CVP). The Tølløfsrud group used colloids intraoperatively, and fluid retention was greater in the crystalloid group only at the end of surgery, but not at 48 hours postoperatively.…”
Section: Blood Loss and Fluid Balancecontrasting
confidence: 50%
“…Lowell and co-workers (1990) demonstrated that after major surgery those patients with a body weight increase of over 20% died, but a moderate fluid overload postoperatively could improve the DO 2 (Arkilic et al 2003) as well as the microcirculation in critically ill patients (Lang et al 2003). Nevertheless, many studies report a better physiological outcome using the optimal model of volume replacement (Tølløfsrud et al 1995, Lobo et al 2002, Brandstrup et al 2003, Nisanevich et al 2005). …”
Section: Principles Of Volume Replacement Therapy After Major Surgerymentioning
confidence: 99%
“…16,17 Several studies that used albumin and HES as priming solutions indicate that conservation of colloid osmotic pressure during CPB reduced the fluid amount accumulated between the tissues. 18 Also, colloidal priming solution usage reduced the total blood volume and intraoperative fluid requirement. 17 Tiryakioglu and colleagues 19 compared the RL and HES 130/0.4 usage as the priming solution on adult patients and observed that BUN and serum creatinine levels were higher in the HES 130/0.4 group at postoperative 24th hour.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The pooled relative risk (RR) was 1.53 (95% CI 1.08-2.13). The albumin treated group carried a risk of death 6% higher than the crystalloid vs.…”
Section: Albumin or Plasma Protein Fraction Crystalloidmentioning
confidence: 99%
“…6,15,16,21,[24][25][26] Four trials used modified gelatins with 95 randomized patients, and the pooled RR was 0.50 (95% CI 0.08-3.03). 6,19,27,28 Eight trials including 668 patients compared dextran with crystalloid and yielded a pooled RR of 1.24 (95% CI 0.94-1.65) (Figure 1). 19,[29][30][31][32][33][34][35] …”
Section: Hydroxyethylstarch Crystalloidmentioning
confidence: 99%